In vitro activities of fleroxacin, cefetamet, ciprofloxacin, ceftriaxone, trimethoprim-sulfamethoxazole, and amoxicillin-clavulanic acid against rare members of the family Enterobacteriaceae primarily of human (clinical) origin. - Hohl, P (1990)
Fleroxacin and cefetamet were evaluated in vitro against 38 infrequently encountered species (250 strains) of the family Enterobacteriaceae and compared with four established compounds. For all the strains tested, the fleroxacin MIC was less than or equal to 0.5 mg/liter, and for 98% of strains the cefetamet MIC was less than or equal to 8 mg/liter; even though the two new compounds did not quite reach the activities (on a weight-by-weight basis) of ciprofloxacin and ceftriaxone, respectively, they nonetheless clearly surpassed trimethoprim-sulfamethaxazole and amoxicillin-clavulanic acid. The very potent new oral compounds tested in this study appear to be promising for the treatment of clinically relevant infections due to uncommon species of Enterobacteriaceae.